Degradation of ciprofloxacin by a constitutive g-C3N4/BiOCl heterojunction under a persulfate system. Issue 7 (2nd February 2023) - Lin, Yingzi; Wang, Yu; Shi, Chunyan; Zhang, Dongyan; Liu, Gen; Chen, Lei; Yuan, Baoling; Hou, Ao; Zou, Deqiang; Liu, Xiaochen; Zhang, Qingyu
Abstract : Ciprofloxacin (CIP) is a third-generation quinolone antimicrobial with broad-spectrum antimicrobial activity, and is not fully metabolized in the human body, resulting in more than 70% of CIP being excreted into water as a prodrug. Abstract : Ciprofloxacin (CIP) is a third-generation quinolone antimicrobial with broad-spectrum antimicrobial activity, and is not fully metabolized in the human body, resulting in more than 70% of CIP being excreted into water as a prodrug. In this study, g-C3 N4 /BiOCl heterojunction structure composites were prepared to study the degradation effect of ciprofloxacin (CIP) under photocatalytic conditions. The results showed that CIP at 10 mg L −1 was best degraded after 90 min at 0.3 g L −1 g-C3 N4 /BiOCl-2, pH of 5.8 and PS dosing of 1 mM. The quenching experiments and electron spin resonance spectroscopy (ESR) confirmed that ˙OH, ˙SO4 − and h + played a major role. After the photocatalytic degradation of this reaction system, the biological toxicity of CIP was effectively controlled. This material is stable and the CIP removal rate remained above 80% after four cycles of experiments.